Selective induction of apoptosis by 7-methyljuglone, its derivatives and isolated compounds from Foeniculum vulgare Mill. on human cancer cells - Lall, Namrita (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.